2018
DOI: 10.3892/ijmm.2018.3507
|View full text |Cite
|
Sign up to set email alerts
|

Ang-(1-7) protects HUVECs from high glucose-induced injury and inflammation via inhibition of the JAK2/STAT3 pathway

Abstract: Angiotensin (Ang)‑1‑7, which is catalyzed by angiotensin‑converting enzyme 2 (ACE2) from angiotensin‑II (Ang‑II), exerts multiple biological and pharmacological effects, including cardioprotective effects and endothelial protection. The Janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) pathway has been demonstrated to be involved in diabetes‑associated cardiovascular complications. The present study hypothesized that Ang‑(1‑7) protects against high glucose (HG)‑induced endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…In addition to epithelial, endothelial, and myocardial cells [ 30 , 31 ], ACE2 is expressed on T lymphocytes [ 32 ], macrophages [ 33 ], and hepatocytes [ [34] , [35] , [36] , [37] ]. ACE2 controls the expression of pro-inflammatory transcription factor Stat3 [ [38] , [39] , [40] , [41] , [42] , [43] ], which also modulates the production of reactive oxygen intermediates by complex I of the mitochondrial electron transport chain (ETC) [ 44 ]. ACE2 also attenuates signaling through mTORC1 [ [45] , [46] , [47] , [48] ] ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to epithelial, endothelial, and myocardial cells [ 30 , 31 ], ACE2 is expressed on T lymphocytes [ 32 ], macrophages [ 33 ], and hepatocytes [ [34] , [35] , [36] , [37] ]. ACE2 controls the expression of pro-inflammatory transcription factor Stat3 [ [38] , [39] , [40] , [41] , [42] , [43] ], which also modulates the production of reactive oxygen intermediates by complex I of the mitochondrial electron transport chain (ETC) [ 44 ]. ACE2 also attenuates signaling through mTORC1 [ [45] , [46] , [47] , [48] ] ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that inhibition of JAK2/STAT3 signal pathway might help prevent LPS-induced inflammation 32,33. Besides, inhibitors of the JAK2/STAT3 pathway have been shown to significantly ameliorate HG/AngII-induced inflammation 34,35. Cupric-ion-oxidized LDL (CuLDL), endothelial cell-oxidized LDL (ELDL) and oxLDL also induced the phosphorylation of JAK2, and then activated STAT3 36.…”
Section: Resultsmentioning
confidence: 99%
“…The preliminary experiment indicated that untreated HUVECs completely formed tubular structures on the Matrigel after 6-8 h of incubation (data not shown). Thus, the tube formation of the HUVECs was observed using a bright-field microscope (magnification, x200) at 6-8 h, as also previously described (34)(35)(36). The branch number and length of the tubes were quantified using ImageJ software (v1.52a; National Institutes of Health).…”
Section: -Ethynyl-2'-deoxyuridine (Edu) Assaymentioning
confidence: 99%